2014
DOI: 10.1371/journal.ppat.1004027
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Related Proteins Control the Flavivirus Infection of Aedes aegypti by Inducing Antimicrobial Peptides

Abstract: The complement system functions during the early phase of infection and directly mediates pathogen elimination. The recent identification of complement-like factors in arthropods indicates that this system shares common ancestry in vertebrates and invertebrates as an immune defense mechanism. Thioester (TE)-containing proteins (TEPs), which show high similarity to mammalian complement C3, are thought to play a key role in innate immunity in arthropods. Herein, we report that a viral recognition cascade compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
143
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 61 publications
4
143
0
Order By: Relevance
“…Hemocytes, which share similarity to mammalian hematogenous cells, are the major cell types in the hemolymph. Although mosquito hemocytes are permissive for the replication of multiple arboviruses [9,67], cellular and humoral immunity in the hemolymph plays an important role in limiting systemic dissemination of arboviruses (Figure 1C) [68]. One of the antiviral mechanisms in the hemolymph is the extracellular phenoloxidase (PO) cascade, which is a humoral immune response that produces cytotoxic intermediates and the formation of melanin following wounding or infection [69,70].…”
Section: The Antiviral Mechanism In the Hemolymphmentioning
confidence: 99%
See 4 more Smart Citations
“…Hemocytes, which share similarity to mammalian hematogenous cells, are the major cell types in the hemolymph. Although mosquito hemocytes are permissive for the replication of multiple arboviruses [9,67], cellular and humoral immunity in the hemolymph plays an important role in limiting systemic dissemination of arboviruses (Figure 1C) [68]. One of the antiviral mechanisms in the hemolymph is the extracellular phenoloxidase (PO) cascade, which is a humoral immune response that produces cytotoxic intermediates and the formation of melanin following wounding or infection [69,70].…”
Section: The Antiviral Mechanism In the Hemolymphmentioning
confidence: 99%
“…In addition to PO-mediated humoral immunity in the mosquito hemolymph, a recent study reported an extracellular pattern recognition mechanism mediated by dual complement-like proteins highly expressed in hemocytes that limited flaviviral infection of A. aegypti by inducing AMPs [68] (Figure 1C). The mammalian complement system is activated during the early phase of viral invasion.…”
Section: The Antiviral Mechanism In the Hemolymphmentioning
confidence: 99%
See 3 more Smart Citations